Offshore coxswain competency evaluation model for internal on-board competency monitoring and assessment - Lim, W.K. (John Wiley and Sons Inc, 2022)
Lifeboats are widely installed on offshore facilities to transfer personnel-on-board to safe location during an emergency. However, an unacceptably high number of incidents that cause serious or fatal injury to the involved crew still occur during routine maintenance and lifeboat drills. Therefore, a competency evaluation model that is suitable for implementation of on-board offshore facilities and produces reliable results is essential. This paper proposes a theoretical competency evaluation model to minimize human error and continuously improve the proficiency of offshore lifeboat coxswains in on-board offshore installations. The offshore coxswain competency evaluation model (OC2EM) is designed in two different sections: Section 1 comprises the base section, and Section 2 comprises the assessment section. OC2EM is assessed with the OPITO Offshore Lifeboat Coxswain Competence Assessment and OPITO Offshore Lifeboat Coxswain Training Standard, which are recognized globally in the oil and gas industry to determine the effectiveness and suitability for implementation. On the basis of the results obtained from the emergency scenarios generated and analysis with the OPITO training and competence standards, OC2EM has proven to be a promising model for implementation in on-board offshore installations because of its capability to be implemented flexibly depending on the requirement of the particular installation while maintaining realistic results. Â© 2022 American Institute of Chemical Engineers